PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT PENGENDALIAN BIAYA PADA PT GARUDA INDONESIA MAKASSAR (PERSERO)Tbk. BRANCH OFFICE MAKASSAR - Ibrahim Ibrahim (AkMen JURNAL ILMIAH, 2018)
The purpose of this study is to determine whether the application of responsibility accounting has been implemented as a means of management control of PT. Garuda Indonesia (Persero) Tbk. Branch Office Makassar. While the method of analysis used in this study is a method of Comparatative Descriptive Approach is to explain and execute comparison of data from the results of two or more studies with different treatment. The results of the research conducted are in the form of data analysis and tables. The results of research with analytical methods implied for accounting accountability in order to run well. accounting liability At PT. Garuda Indonesia (Pesero) Tbk. Branch Office Makassar has a very important role in management control that is to motivate managers in each division, while accounting information is part of the company needed to determine the attitude or purpose of central management budget and realization. Manager activity is also directly monitored from the accounting information created, in this case the accountability report.